Compreensão da experiência do sofrimento de mulheres na relação amorosa - Moreira, Ana Regina de Lima (2004)
Our professional everyday life, as a psychologist, we often come across the narrative made by women of a permanent suffering experience in loving and sexual relation. This checking created questions which indicated to the questioned experience singularity, taking into account the historic and cultural aspects (genre and romantic love) that seemed to permeate such an experience. The conduction given to this research was guided by the following question: how is to the woman the experience of going on suffering on loving and sexual relation? Therefore, the objective was to understand that experience. Were carried out with six women that were living the experience which intend to investigate. The narrative, in according to the purposal by Walter Benjamin was the access tool to the experience. The narrative analysis shows the singularity of constant suffering experience on loving relation as well as common aspects. It is remarkable the presence of relative questions to the genre and romantic loving dimension, influencing the way as the interviewed women perceive themselves on the existence and realize the loving suffering which experience. Women reveal several ways of expressing and perceiving to the loving suffering which is common the manifestation of several physical and psychic symptoms. The most participants had experiences of protected familiar contact of feeling development of low self-esteem, disability, unstableness and fear. We realize that the suffering of interviewed women, on loving relation, it revels, above all, a way of being in the world, perveiving themselves, marked by solitude fear, lovelessness, leading the life itself giving origin to the lifestyle and of really new loving. Thus, we emphasize the importance of greater engagement of professionals and institutions which deal with the thematic this research in order to develop actions that consider its complexity. We also emphasize new reflections about the loving suffering so that different sense possibilities can emerge propitiating a greater comprehension of human subjectivity